The MNESIS model: Memory systems and processes, identity and future thinking. (1st July 2016) - Eustache, Francis; Viard, Armelle; Desgranges, Béatrice
Abstract: The Memory NEo-Structural Inter-Systemic model (MNESIS; Eustache and Desgranges, Neuropsychology Review, 2008) is a macromodel based on neuropsychological data which presents an interactive construction of memory systems and processes. Largely inspired by Tulving's SPI model, MNESIS puts the emphasis on the existence of different memory systems in humans and their reciprocal relations, adding new aspects, such as the episodic buffer proposed by Baddeley. The more integrative comprehension of brain dynamics offered by neuroimaging has contributed to rethinking the existence of memory systems. In the present article, we will argue that understanding the concept of memory by dividing it into systems at the functional level is still valid, but needs to be considered in the light of brain imaging. Here, we reinstate the importance of this division in different memory systems and illustrate, with neuroimaging findings, the links that operate between memory systems in response to task demands that constrain the brain dynamics. During a cognitive task, these memory systems interact transiently to rapidly assemble representations and mobilize functions to propose a flexible and adaptative response. We will concentrate on two memory systems, episodic and semantic memory, and their links with autobiographical memory. More precisely, we will focus on interactions between episodic and semantic memory systems in support of 1) self-identity in healthy aging and in brain pathologies and 2) the concept of the prospective brain during future projection. In conclusion, this MNESIS global framework may help to get a general representation of human memory and its brain implementation with its specific components which are in constant interaction during cognitive processes. Highlights: MNESIS comprises five memory systems by integrating the concepts developed by Tulving (1995, 2001), Baddeley (2000). MNESIS highlights relations between different systems to illustrate the dynamic and reconstructive nature of human memory. The focus will be on interactions between episodic and semantic memory systems in autobiographical memory and future thinking. Neuropsychological data and neuroimaging findings will be reviewed in healthy aging and in brain pathologies (Alzheimer's disease and semantic dementia).